Efektivitas Pendidikan Gizi Metode Ceramah dan Audio Visual terhadap Pengetahuan dan Sikap tentang Pencegahan Stunting pada Wanita Usia Subur Pranikah - Dwi Hartanti (Universitas Islam Negeri Walisongo Semarang, 2021)
The purpose of this study was to determine the effectiveness of the lecture and audio-visual nutrition education methods on knowledge and attitudes related to stunting prevention in women of childbearing age. This research is true experimental design with One Group Pretest Posttest Design. The sample was 77 female students of the Psychology Study Program, Faculty of Psychology and Health, UIN Walisongo, ranging in age from 18-25 years. The intervention was using nutrition education with combination of lecture and audiovisual methods. Knowledge and attitudes were measured using a questionnaire that has been assessed validity and reliability. Statistic Test was using Paired t-test. There was a significant difference between the average scores of knowledge and attitudes of subjects before the intervention (pretest) and after the intervention (posttest). The maverage score of the subject's knowledge before the intervention was 8.97 (59.8% of the questions were answered correctly) and the maverage score of the subject's knowledge after the intervention was 12.57 (83.8% of the questions were answered correctly). The average score of the subject's attitude before the intervention was 43.2% and 81.1% after the intervention. The conclusion is that there is a significant influence on the average differences of knowledge and attitudes score before and after the intervention. Penelitian ini bertujuan untuk mengetahui efektivitas pendidikan gizi metode ceramah dan audio visual terhadap pengetahuan dan sikap terkait pencegahan stunting pada wanita usia subur. Penelitian dengan desain true experimental dengan rancangan one group pretes-postest design. Sampel adalah mahasiswi perempuan Prodi Psikologi Fakultas Psikologi dan Kesehatan UIN Walisongo sebanyak 77 subyek dengan rentang usia 18-25 tahun. Intervensi berupa pendidikan gizi dengan metode ceramah dan audiovisual. Pengetahuan dan sikap diukur menggunakan kuesioner yang telah diuji validitas dan reliabilitas. Uji beda dilakukan menggunakan Uji paired t-test. Hasil statistik menunjukkan bahwa ada perbedaan yang signifikan antara rerata skor pengetahuan dan sikap subjek sebelum intervensi (pretest) dan setelah intervensi (posttest). Rerata skor pengetahuan subjek sebelum intervensi adalah 8,97 (59,8% pertanyaan dijawab benar) dan rerata skor pengetahuan subjek setelah intervensi adalah 12,57 (83,8% pertanyaan dijawab benar). Rerata skor sikap subjek sebelum intervensi adalah 49,2% dan 81,1% setelah dilakukan intervensi. Simpulan penelitian ini adalah terdapat pengaruh yang bermakna terhadap perbedaan rerata skor pengetahuan dan sikap sebelum dan setelah intervensi.